“Don’t be stupid.” The role of social media policies in journalistic boundary-setting - Duffy, Andrew (2019)
Social media are now firmly embedded in professional newsrooms, and policies and guidance within these newsrooms have evolved to include social media activities. These policies articulate and expose the underlying assumptions of the role of these new media within the traditional boundaries of the newsroom. Through thematic analysis of the policies of 17 news organizations, this research identifies and explicates the ways in which professional news organizations have moved and reinforced the boundaries of newswork to both include social media, and to bring social media under its control—to the extent of requiring newsworkers to subsume their personal online identities under their professional ones. The research identifies a number of areas of further research, including analysis of compliance with these policies and resistance to them on the part of newsworkers.